The role of serum amyloid A staining of granulomatous tissues for the diagnosis of sarcoidosis. (May 2017) - Huho, Albert; Foulke, Llewellyn; Jennings, Timothy; Koutroumpakis, Efstratios; Dalvi, Siddhartha; Chaudhry, Haroon; Chopra, Amit; Modi, Aakash; Rane, Neha; Prezant, David J.; Sheehan, Christine; Yucel, Recai; et al.
Abstract: Background: Previous studies demonstrated that SAA staining of sarcoidosis granulomas was qualitatively and quantitatively different from other granulomatous diseases. These data suggest that positive SAA staining of granulomatous tissue may have adequate specificity to establish a diagnosis of sarcoidosis. Our objective was to determine the diagnostic specificity of SAA staining for sarcoidosis relative to other granulomatous disorders. Methods: Pathological specimens demonstrating granulomatous inflammation were retrospectively identified at one institution, plus 4 specimens were obtained from New York City firefighters with biopsy-confirmed World Trade Center "sarcoidosis-like" pulmonary disease. Specimens were analyzed if specific diagnoses related to the granulomatous inflammation were confirmed through medical record review. SAA staining was performed using previously developed methods. Two pathologists, blinded to each other and the diagnoses, determined if the stained material was SAA positive or negative. Discordant results were adjudicated by the two pathologists. Measurements and main results: 106 specimens were analyzed from 100 patients, with 36 biopsies (34%) from sarcoidosis tissues and 70 (66%) from other granulomatous disorders. The Cohen Kappa correlation between the two pathologists for SAA staining positivity was excellent (0.85, 0.73–0.98). The overall specificity of SAA staining for the diagnosis of sarcoidosis was 84% (59/70). The sensitivity was 44% (16/36). Conclusions: Although SAA staining of various granulomatous tissues was fairly specific for the diagnosis of sarcoidosis, the specificity was inadequate for SAA staining to be used as a diagnostic test for sarcoidosis in isolation. These data suggest that SAA production may not be a universal mechanism in the development of sarcoidosis. Highlights: We performed an analysis of SAA staining for the diagnosis of sarcoidosis. The diagnostic specificity of SAA staining was inadequate as an isolated diagnostic test. A positive SAA stain does raise the clinical suspicion of sarcoidosis. These data suggest that SAA is not necessary for the development of sarcoidosis.